1998
DOI: 10.1038/sj.jhh.1000656
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the elderly: attitudes of British patients and general practitioners

Abstract: The perceptions of patients and GPs of the risk of stroke in treated and untreated elderly hypertensives, and their attitudes towards anti-hypertensive therapy were examined. To explore attitudes of patients to the management of hypertension a qualitative approach was used, employing semi-structured interviews, with subsequent thematic analysis of the transcriptions. A questionnaire study of GPs' attitudes to the same subject was also conducted.The elderly (n ‫؍‬ 75) greatly overestimate the risks of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…We have reported the attitudes of patients to treatment of hypertension in an earlier paper. 6 Barriers to the effective implementation of current research findings were identified, some of which are immutable, but many can be overcome. The identification of such barriers is an important first step in the process of getting research results into practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported the attitudes of patients to treatment of hypertension in an earlier paper. 6 Barriers to the effective implementation of current research findings were identified, some of which are immutable, but many can be overcome. The identification of such barriers is an important first step in the process of getting research results into practice.…”
Section: Discussionmentioning
confidence: 99%
“…4 We have also shown that GPs currently are undertreating hypertension 5 and, despite being aware of the risks of hypertension in the elderly and the benefits of its treatment, 6 fewer than half comply with the broad recommendations of even the most conservative evidencebased guidelines. 6,7 Yet good management of hypertension in the elderly is one of the most effective and costeffective ways of preventing heart disease and stroke, 8,9 and is a key objective in public health policy today. 10 This study is part of a larger project investigating the important issues that influence GPs in their management of hypertension in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…29,34 Aside from patients' own experiences, information from surrounding people is reported by several authors as influential on expectations. Doctors' advice 30,35 is balanced with personal and vicarious experiences, 25 whereas academics and pharmaceutical industry are seen as less reliable sources. 36 Development of trust in a prescriber seems to influence patients' decision to accept treatment, suggesting that it leads to expectations of beneficial effects, 28,36 while patients that retain a more critical stance compare prescribing to experimentation and question the doctor's knowledge about how a specific patient's body works.…”
Section: 37mentioning
confidence: 99%
“…Patients wish for guarantees of survival [30][31][32][33] 2. Experiences and evaluation develop over time Duration of illness influences understanding of disease and treatment effects 26,34 Past bad experiences of side-effects triggers a conscious evaluation of risks and benefits when new treatments are suggested 26 Patients are seeking to confirm and adjust expectations 26,28 One's own experiences and those of other people are used in decisions about medicines 24,25,28,29,[34][35][36] Risks and benefits are balanced by patients in a different way than by doctors 26,[29][30][31][32] 3.…”
Section: 31mentioning
confidence: 99%
See 1 more Smart Citation